Perbandingan Keakuratan Model Laba Permanen, Transitori Dan Agregat Dalam Memprediksi Laba Masa Depan - Galuh Artika Febriyanti (BIP's JURNAL BISNIS PERSPEKTIF, 2017)
Earnings represent information which very paid attention by users of financial statements. Some research was examined the ability of earnings to forecast future earnings which only focused to aggregate earnings. Some literature mention that reported earnings number contain permanent and transitory earnings component which can be used to forecast future earnings and future cash flow. Permanent earnings is earnings related to core activity of the firms which always happened each every period, while transitory earnings are earnings do not relate with core activity of the firms and is not expected to happened in next period. This research empirically examines the level of accuracy model with permanent, transitory, and aggregate earnings component to forecast future earnings of the firms